Political writings - Constant, Benjamin (Cambridge texts in the history of political thought., 1988)
This 1988 book is an English translation of the major political works of Benjamin Constant, one of the most important of modern French political theorists and writers. A Swiss protestant by birth, Constant was a prominent figure in French political life in the aftermath of the revolution of 1789, and a leading member of the liberal opposition to Napoleon and, subsequently, to the restored Bourbon monarchy. His writings are widely regarded as one of the classical formulations of modern liberal doctrine, and Constant's own closeness to the Anglo-Saxon political tradition renders their translation into English particularly appropriate. The novel Adolphe has hitherto been Constant's only work freely available outside France, emphasising his importance within European Romanticism and his centrality to French literary development in the nineteenth century. This translation of Constant's political writings is replete with full editorial apparatus and bibliographic information that will enable anglophone students of liberal thought to engage at first hand with one of its most durable and influential exponents.